Kepercayaan Publik sebagai Determinan Partisipasi Filantropi Ekonomi - Bahrul Anam Albasri (Asian Journal of Multidisciplinary Research, 2026)
This study addresses the problem that public participation in economic philanthropy tends to fluctuate when public trust declines. The study aims to examine public trust as a determinant of participation in economic philanthropy by clarifying the relationships among the concepts of determinants, economy, and the public. Using a qualitative library-based research design, the study synthesizes relevant books, journals, and prior academic reports through systematic literature reading and content analysis to identify recurring patterns and conceptual linkages. The data consist of key findings extracted from literature that discusses how trust is formed through transparency, accountability, and verifiable economic impact signals, and how these signals shape participation decisions. The study concludes that public trust is a central mechanism that reduces perceived risk and increases perceived certainty of benefits, thereby driving sustained participation in economic philanthropy.